Internet connectivity disruption in Algeria (Algeria) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Algeria. Data sourced from IODA.
Network Disruption Incident ID: DZ-2026-0054. Severity: critical. Confidence: 65%